Downregulation of microRNA-512-3p enhances the viability and suppresses the apoptosis of vascular endothelial cells, alleviates autophagy and endoplasmic reticulum stress as well as represses atherosclerotic lesions in atherosclerosis by adjusting spliced/unspliced ratio of X-box binding protein 1 (XBP-1S/XBP-1U). Issue 2 (20th December 2021) - Ge, Peipei; Gao, Mingxiao; Du, Juan; Yu, Jingbin; Zhang, Lei
ABSTRACT: AS is an important pathological basis of cardiovascular disease. miRNAs are involved in almost all steps of AS, including the injury and dysfunction of endothelial cells and vascular smooth muscle cells. This work elucidated the biological functions of miR-512-3p in AS and probed into the underlying molecular mechanism. In the present work, ox-LDL-treated HUVECs served as the in vitro model of AS and ApoE-/- mice were nourished with a high-fat diet to establish an in vivo model of AS. Proliferation, apoptosis, and migration of HUVECs were evaluated by CCK-8, TUNEL staining, Western blot, and transwell assays. Immunofluorescence examined LC3 expression and levels of autophagy-related and ER stress-related proteins were determined by Western blot assay. In addition, starBase predicted the complementary binding sites of XBP-1 to miR-512-3p and luciferase reporter assay confirmed the interaction between miR-512-3p and XBP-1. Moreover, H&E staining was employed to evaluate atherosclerotic lesions in AS model mice. Results revealed that ox-LDL treatment decreased the proliferative and migrative activities and promoted the apoptosis of HUVECs as well as induced autophagy and ER stress, which were abrogated by miR-512-3p silencing. Importantly, ox-LDL treatment elevated miR-512-3p expression and XBP-1 was a direct target of miR-512-3p. Mechanistically, knockdown of miR-512-3p enhanced the viability, suppressed the apoptosis, and promoted the migration of ox-LDL-treated HUVECs, alleviated atherosclerotic lesions in AS model mice as well as repressed autophagy and ER stress by targeting XBP-1 to manipulate the ratio of XBP-1S/XBP-1 U.